2020
DOI: 10.1111/gcb.14962
|View full text |Cite
|
Sign up to set email alerts
|

Microbial carbon limitation: The need for integrating microorganisms into our understanding of ecosystem carbon cycling

Abstract: Numerous studies have demonstrated that fertilization with nutrients such as nitrogen, phosphorus, and potassium increases plant productivity in both natural and managed ecosystems, demonstrating that primary productivity is nutrient limited in most terrestrial ecosystems. In contrast, it has been demonstrated that heterotrophic microbial communities in soil are primarily limited by organic carbon or energy. While this concept of contrasting limitations, that is, microbial carbon and plant nutrient limitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
179
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(200 citation statements)
references
References 104 publications
14
179
3
4
Order By: Relevance
“…Reduced belowground C allocation by plants may suppress microbial enzyme production due to C and energy limitations of microbial metabolism and growth over time (Mooshammer, Wanek, Zechmeister-Boltenstern, & Richter, 2014;Soong et al, 2019). This explanation is supported by our finding that N loading increases microbial specific phosphatase expression in the short-term, but not in the long-term.…”
Section: Acclimation Of Soil Phosphatase Activity To Prolonged N Losupporting
confidence: 70%
See 1 more Smart Citation
“…Reduced belowground C allocation by plants may suppress microbial enzyme production due to C and energy limitations of microbial metabolism and growth over time (Mooshammer, Wanek, Zechmeister-Boltenstern, & Richter, 2014;Soong et al, 2019). This explanation is supported by our finding that N loading increases microbial specific phosphatase expression in the short-term, but not in the long-term.…”
Section: Acclimation Of Soil Phosphatase Activity To Prolonged N Losupporting
confidence: 70%
“…Thus, it is likely that there is an ecosystem‐specific threshold, above which prolonged N inputs do not exacerbate the P limitation, but instead reduce belowground C allocation (Tian, Wang, Sun, & Niu, 2016). Reduced belowground C allocation by plants may suppress microbial enzyme production due to C and energy limitations of microbial metabolism and growth over time (Mooshammer, Wanek, Zechmeister‐Boltenstern, & Richter, 2014; Soong et al., 2019). This explanation is supported by our finding that N loading increases microbial specific phosphatase expression in the short‐term, but not in the long‐term.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no OTUs separated the control from the synthetic fertilizer treatment. The soil bacterial communities are primarily organic C limited, and only secondarily N limited (Soong et al, 2020), which may explain the similarity of the communities in the control and the synthetic fertilizer treatment. According to the report from Fierer et al (2007), the continuous C input in the organic fertilizer treatment may have contributed to the higher abundances of the copiotrophic Bacteroidetes OTUs.…”
Section: Discussionmentioning
confidence: 96%
“…With elevated N input or across a N gradient, the community composition became progressively more distinct at higher N levels from those at no or lower levels of N fertilizer (Ramirez et al, 2010;Fierer et al, 2012). In addition, Soong et al (2020) reported that soil organic carbon (C) content is the primary limitation for heterotrophic microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in this study, we observed a strong positive correlation between EcM relative abundance and free-living microbial CUE. This positive response could have been driven by considerable EcM exudate secretion to the surrounding microbial community (Phillips and Fahey, 2006;Frey, 2019), outweighing the potential negative effects of nutrient competition between the free-living community and EcM (Phillips and Fahey, 2005;Fransson et al, 2016;Soong et al, 2020). This mechanism is further supported by a study which found that EcM exudate production decreased under elevated soil N conditions, followed by a decrease in microbial growth and biomass (Gorka et al, 2019).…”
Section: Carbon Use Efficiencymentioning
confidence: 89%